ABILITY TO WRITE CALLIGRAPHY ARABIC LITERATURE STUDENTS AT THE INDONESIAN MUSLIM UNIVERSITY MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study focuses on the ability to write Arabic calligraphy of Arabic literature students at the Indonesian Muslim University. The purpose of this study was to find out how students' ability to write calligraphy of Arabic literature at the Muslim University of Indonesia is, and what are the factors that influence the ability of Arabic literature students at the Indonesian Muslim University to write calligraphy in Naski script. The population used in this study were all students of Arabic literature. The sample is 6th semester students. This research is a qualitative descriptive study, using data collection techniques through observation, tests, questionnaires and interviews. The conclusion of this study is that the ability to write Arabic calligraphy for Arabic literature students at the Indonesian Muslim University Makassar is categorized as "Poor". With a percentage of 61.75%. The factors that affect the ability of students to write calligraphy are: 1. There is still a lack of student equipment in learning calligraphy, both from the campus and from the students themselves. 2. There is still a lack of students repeating or practicing calligraphy at home. 2. There are still many students who have difficulty learning calligraphy due to their educational background from public schools who do not study calligraphy. 3. The calligraphy material provided is not optimal in full because it is only a specialization course. The factors that affect the ability of students to write calligraphy are: 1. There is still a lack of student equipment in learning calligraphy, both from the campus and from the students themselves. 2. There is still a lack of students repeating or practicing calligraphy at home. 2. There are still many students who have difficulty learning calligraphy due to their educational background from public schools who do not study calligraphy. 3. The calligraphy material provided is not optimal in full because it is only a specialization course. The factors that affect the ability of students to write calligraphy are: 1. There is still a lack of student equipment in learning calligraphy, both from the campus and from the students themselves. 2. There is still a lack of students repeating or practicing calligraphy at home. 2. There are still many students who have difficulty learning calligraphy due to their educational background from public schools who do not study calligraphy. 3. The calligraphy material provided is not optimal in full because it is only a specialization course. There are still many students who have difficulty learning calligraphy due to their educational background from public schools who do not study calligraphy. 3. The calligraphy material provided is not optimal in full because it is only a specialization course. There are still many students who have difficulty learning calligraphy due to their educational background from public schools who do not study calligraphy. 3. The calligraphy material provided is not optimal in full because it is only a specialization course.